CTRP3 Protects against High Glucose-Induced Cell Injury in Human Umbilical Vein Endothelial Cells - Fang Wang; Linlin Zhao; Yingguang Shan; Ran Li; Guijun Qin (Analytical Cellular Pathology)
Aims. Inflammation was closely associated with diabetes-related endothelial dysfunction. C1q/tumor necrosis factor-related protein 3 (CTRP3) is a member of the CTRP family and can provide cardioprotection in many cardiovascular diseases via suppressing the production of inflammatory factors. However, the role of CTRP3 in high glucose- (HG-) related endothelial dysfunction remains unclear. This study evaluates the effects of CTRP3 on HG-induced cell inflammation and apoptosis. Materials and Methods. To prevent high glucose-induced cell injury, human umbilical vein endothelial cells (HUVECs) were pretreated with recombinant CTRP3 for 1 hour followed by normal glucose (5.5 mmol/l) or high glucose (33 mmol/l) treatment. After that, cell apoptosis and inflammatory factors were determined. Results. Our results demonstrated that CTRP3 mRNA and protein expression were significantly decreased after HG exposure in HUVECs. Recombinant human CTRP3 inhibited HG-induced accumulation of inflammatory factors and cell loss in HUVECs. CTRP3 treatment also increased the phosphorylation levels of protein kinase B (AKT/PKB) and the mammalian target of rapamycin (mTOR) in HUVECs. CTRP3 lost its inhibitory effects on HG-induced cell inflammation and apoptosis after AKT inhibition. Knockdown of endogenous CTRP3 in HUVECs resulted in increased inflammation and decreased cell viability in vitro. Conclusions. Taken together, these findings indicated that CTRP3 treatment blocked the accumulation of inflammatory factors and cell loss in HUVECs after HG exposure through the activation of AKT-mTOR signaling pathway. Thus, CTRP3 may be a potential therapeutic drug for the prevention of diabetes-related endothelial dysfunction.